Wrodzone zarośnięcie krtani i przełyku u dziewczynki z delecją 22q11.2 - opis przypadku - Komasinska, Paulina; Szczawińska-Popłonyk, Aleksandra; Jończyk-Potoczna, Katarzyna; Bręborowicz, Anna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
DiGeorge Syndrome (DGS) is the result of microdeletion in the 22q11.2 region, with broad spectrum of clinical manifestations, but the most characteristic features are congenital heart disease, thymic, parathyroid hypoplasia or aplasia, which may cause T-cell immune deficiency and hypocalcemia. We report on the case of 3.5-year-old girl with DGS, esophageal and laryngeal atresia because of the rarity of this combination and for the purpose to underline the role of early endoscopic examination of airways, especially before surgery in this group of patients.